Thermal stability of solid and aqueous solutions of humic acid - Kolokassidou, C.; Pashalidis, Ioannis; Costa, Costas (My University, 2007)
The effects of temperature on the stability of a soil humic acid were studied in the present work. Solid samples of Gohy-573 humic acid (HA) and dissolved ones in aqueous solution (pH 6.0, 0.1 mol L−1 NaClO4) were investigated in order to understand the impact of temperature on the chemical properties of the material. The methods applied to solid samples in the present investigation were thermogravimetric analysis (TGA), temperature-programmed desorption coupled with mass spectrometry (TPD–MS), and in situ diffuse reflectance infrared Fourier transformed spectroscopy (in situ DRIFTS). Humic acid samples were studied in the 25–800 ◦C range, with focus on thermal/chemical processes up to 250 ◦C. The reversibility of the changes observed was investigated by cyclic changes to specified temperature ranges (40–110 ◦C). All measurements were conducted under inert-gas atmosphere in order to avoid samples combustion at increased temperatures. Aqueous solutions were analyzed by UV–vis absorption spectroscopy after storage at temperatures up to 95 ◦C, and storage times up to 1 week. For temperatures below 100 ◦C experiments on solid and aqueous samples have shown results which were consistent to each other. The amount of water desorbed is temperature dependent and up to 70 ◦C this process was totally reversible. Above 70 ◦C an irreversible loss of water was also observed, which according to UV–vis spectroscopy corresponds to water produced by condensation leading to more condensed polyaromatic structures. The water released up to 110 ◦C was about 7 wt% of the total mass of the dried humic acid, where less than 50% corresponded to reversibly adsorbed water. At higher temperatures (>110 ◦C), gradual decomposition resulting in the formation of carbon dioxide (110–240 ◦C), and carbon monoxide (140–240 ◦C) takes place. Hence, thermal treatment of Gohy-573 humic acid above 70 ◦C results in irreversible structural changes, that could affect chemical properties (e.g., complex formation) of the material.
Keywords: Humic acid; Thermogravimetry; Fourier transform infrared spectroscopy; Mass spectrometry; Spectroscopy